Research on health education and health promotion during the process of schistosomiasis elimination III new approaches for student health education. - Jing Zhang; Dandan Lin; Fei Hu; Dong Li; Junjiang Chen; Hua Xie; Yifeng Li; Sheng Ding (PLoS Neglected Tropical Diseases)
Schistosomiasis remains a critical public health challenge in endemic regions, particularly among school-aged children. Despite global efforts, conventional health education approaches show limited success in translating knowledge into sustained practices change. This study evaluates the efficacy of two innovative educational approaches-curriculum-integrated infiltration and stepwise progressive approaches-compared to traditional methods in enhancing schistosomiasis-related knowledge, attitudes, and practices (KAP) among students. A school-based intervention was conducted in Duchang County's Zhouxi township, with is an area afferted by schistosomiasis in China. Sixth-grade students (n ≈ 300) were divided into three groups: a traditional intervention group receiving standard WHO-aligned lectures, an infiltration group with cross-disciplinary curriculum integration, and a stepwise group with modular, tiered content. KAP outcomes were assessed via validated questionnaires at baseline and post-intervention. Both intervention groups demonstrated significant knowledge gains compared to traditional intervention (post-intervention accuracy: infiltration 89.67%, stepwise 91.10%, traditional intervention 86.50%; P < 0.001). Practices knowledge showed the most significant improvement (41.47% increase in the infiltration group vs. 22.38% in traditional intervention). The stepwise approaches achieved the highest overall accuracy (91.10%) but showed no statistically significant advantage over the infiltration approach (P > 0.05). Attitudinal improvements were consistent across groups, with high baseline rates limiting further gains (post-intervention: 95.60-96.68%). Curriculum-integrated and stepwise approaches effectively address the knowledge-practices gap in schistosomiasis education. The infiltration strategy, requiring minimal resources, is ideal for practices reinforcement in low-resource settings, while the stepwise approach suits rapid knowledge dissemination in well-resourced areas. These findings advocate for context-adaptive, multisectoral frameworks to optimize school-based interventions, aligning with WHO goals for neglected tropical disease elimination.